The Comparative Dialectic of Islam, Politics, and Government in Indonesia and Thailand - Marom, Ahmad Anfasul; Kusuma, Bayu Mitra Adhyatma (Pusat Studi Pesantren dan Pemberdayaan Masyarakat, LPPM, Universitas Brawijaya, 2019)
The religion particularly Islam has a considerable influence on the politics and governmental system in a country generally. But of course the role of Islam in politics and government will be different when Islam as the majority religion compared when Islam became a minority religion. It becomes interesting to be explored further, so as to see concrete evidence the authors determined to compare the dialectic of Islam in the politics and government in Indonesia and Thailand. The results of research showed that there is a significant imbalance between the role of Islam in Indonesia and Thailand for politics and government. In Indonesia since the struggle until independence era, the Muslim leaders and activists are aware that in order to improve the condition of the country, it takes a political struggle to deal with attempts to obtain power to influence government and public policy making. This can be evidenced by the existence of Islamic party or Islamic mass-based party from the first general election to date. In addition, at the level of government the role of Muslim activists and scholars are also greatly affected. Instead, in Thailand show that Islam has a small portion in politics and government. This is evidenced by the lack of political access and opportunity to participate in the governmental system. Even in a particular regime, Muslims get very discriminatory treatment. Like as in the administration of Prime Minister Phibul Songkhram and Thaksin Shinawatra. This condition is supported by the prevailing political system in Thailand, where the authority of the regime is absolute and inviolable. As an impact, insurgents groups in Southern Thailand namely National Revolution Row (BRN) and Pattani United Liberation Organization (PULO) continued to express special autonomy. With the special autonomy it is expected that the conflict in Southern Thailand will subside.